The detrimental effects of progression of retinal degeneration in the visual cortex - Bhattacharyya, Anwesha (Frontiers in Cellular Neuroscience, 2022)
The leading cause of blindness in inherited and age-related retinal degeneration (RD) is the death of retinal photoreceptors such as rods and cones. The most prevalent form of RD is age related macular degeneration (AMD) and retinitis pigmentosa (RP). Several approaches have been developed in recent years to artificially stimulate the remaining retinal neurons by adeno- associated viral (AAV) vector-based delivery of light sensitive proteins into surviving retinal cells. However, the outcome of these strategies have been limiting. The success of these treatments relies on the morphology, physiology, and proper functioning of the remaining intact structures in the downstream visual pathway. It is not completely understood what all alterations occur in visual cortex during RD. In this review I will discuss the known information in literature about morphological and functional changes that occur in the visual cortex in rodents and humans during RD. The aim is to highlight the changes in visual cortex that are crucial for developing tools directed towards restoration of high-resolution vision in patients with visual impairment.